Menyoroti Konflik dan HAM di Papua dalam Debat Capres 2024 di Kompas.com dari Perspektif Analisis Wacana Kritis - Ayu Bandu Retnomurti; Ratna Dewanti (Pusat riset dan Inovasi Nasional, 2025)
This study analyzes Kompas.com’s news coverage of the Papua conflict and human rights issues during the 2024 Presidential Debate to examine media neutrality through Norman Fairclough’s Critical Discourse Analysis (CDA) integrated with Teun A. Van Dijk’s model. The analysis covers three dimensions: micro (text), meso (discursive practice), and macro (social practice), using a qualitative descriptive method. Data from 21 news excerpts reveal that social and political contexts are clearly represented, focusing on the strategies of the three presidential candidates in addressing human rights and conflict issues in Papua. The findings highlight the importance of realizing the Papua-related commitments made during the debate by the elected president, given the rising trend of violence and the unresolved justice issues in the region. The study demonstrates that media coverage, even by a leading news outlet such as Kompas.com, carries the potential to influence public perception regarding sensitive political and social issues. At the micro level, the language and lexical choices in the news articles often convey subtle ideological positions, including the framing of human rights violations and conflict events, which may reflect both explicit and implicit biases. At the meso level, discursive practices, including editorial decisions, headline constructions, and sourcing patterns, contribute to the shaping of narratives, highlighting certain aspects of the candidates’ statements while minimizing others. Meanwhile, at the macro level, the broader societal and political context, including historical grievances, regional tensions, and national political dynamics, provides the backdrop against which news coverage is produced and consumed, indicating the complex interplay between